SIKAP MASYARAKAT BERHUBUNGAN DENGAN KEPATUHAN DALAM PENERAPAN 3M PENCEGAHAN COVID-19 - Muskhab Eko Riyadi; Anna Nur Hikmawati; RR.Viantika Kusumasari (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2022)
The health problem that is currently receiving global attention is the Covid-19 disease. Coronavirus disease first appeared in December 2019 in Wuhan City, China. The United States is still the country with the most cases, namely 3,896,855 cases of coronavirus infection, Indonesia is ranked 25th, the number of cases in Indonesia is still above China and below Egypt which recorded 87,775 cases, while Bantul Regency occupies the highest case in DI. Yogyakarta Province, where the active status is 30,366. One of the most important things to consider in the context of handling Covid-19 cases is how the public's attitude towards Covid-19. The research aims to determine the relationship between community attitudes and community compliance in the application of 3M. This is a non-experimental study with a cross-sectional research design. The population in this study is the community in Potorono Village, Banguntapan, Bantul, DI. Yogyakarta. The sampling technique used a consecutive sampling technique and obtained a large sample of 80 respondents. Statistical test using Chi-Square test. The results of this study indicate that the attitude of the community is mostly in the good category and community compliance in the application of 3M is in the obedient category, while the results of statistical tests obtained a p-value of 0.000 (p<0.05). Conclusion ; there is a relationship between people's attitudes and compliance in the application of 3M. We advise the public to maintain compliance with 3M implementation.